Advertisements of follow-on formula and their perception by pregnant women and mothers in Italy. Issue 4 (15th December 2014) - Cattaneo, Adriano; Pani, Paola; Carletti, Claudia; Guidetti, Margherita; Mutti, Valentina; Guidetti, Cecilia; Knowles, Alessandra; ,
Abstract : Objective: To assess how follow-on formula milks for infants aged 6–12 months are presented to and understood by mothers. Design: A quantitative and qualitative cross-sectional study including (1) an analysis of advertisements in three magazines for parents; (2) in-depth semistructured qualitative interviews to pregnant women on their perception of two advertisements for follow-on formula and (3) self-administered questionnaires for mothers to explore their exposure to and perception of formula advertisements. Participants: Eighty pregnant women 32–36 weeks of gestation with no previous children and 562 mothers of children <3 years old. Setting: Maternal and child health centres in eight cities of Italy. Results: Advertisements of formula (n=89) represented about 7% of all advertisements in the three magazines, the majority (58%) being for follow-on formula. Advertisements were parent-oriented, aimed at helping parents solve health problems of their babies or at eliciting good feelings, or both. The qualitative interviews to pregnant women showed inability to define the advertised products at first glance due to the ambiguity of the numeral 2 and the presumed age of the portrayed baby; this inability did not disappear after carefully viewing the advertisements and reading the text. When asked in the self-administered questionnaires whether they had ever come across advertisements of infant formula, 81% of mothers reported that they had, despite the legal inexistence of such advertisements, and 65% thought that it was for a product to be used from birth. Conclusions: Advertisements of follow-on formula are perceived by pregnant women and mothers as promoting infant formula.